Preliminary results of clinical, biochemical, and radiological investigation into the oxidative status in patients with rotator cuff tendinopathy - Cemil Ertürk; Gürkan Çalışkan; Özcan Erel (Acta Orthopaedica et Traumatologica Turcica)
Objective: We investigated oxidative status in patients with rotator cuff tendinopathy (RCT) and evaluated their relationship with radiological and clinical parameters.